2021
DOI: 10.3390/rs13163141
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Soil Organic Carbon Contents in Croplands of Bavaria from SCMaP Soil Reflectance Composites

Abstract: For food security issues or global climate change, there is a growing need for large-scale knowledge of soil organic carbon (SOC) contents in agricultural soils. To capture and quantify SOC contents at a field scale, Earth Observation (EO) can be a valuable data source for area-wide mapping. The extraction of exposed soils from EO data is challenging due to temporal or permanent vegetation cover, the influence of soil moisture or the condition of the soil surface. Compositing techniques of multitemporal satell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 87 publications
2
31
1
Order By: Relevance
“…Group "i" was the most represented, while group "ii" is just emerging [55]. Group "iii", referred to as a "bottom up" approach by Castaldi et al [108,109], was developed at the regional scale (e.g., in a loam belt region in Belgium and in the Gutland-Oesling region in Luxembourg [48] and Bavaria (Germany) [74]), at the national scale (e.g., Spain [75]), and then at the supranational, continental scales (e.g., European scale [57,76]) using the LUCAS alone [57,75,76] or in combination with a local database [74,77] and also at the scale of Canada using the CanSYS National Pedon Database [78]. As they are directly derived from the spectral features, we focus on the first three groups.…”
Section: Approaches Conducted and Their Performancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Group "i" was the most represented, while group "ii" is just emerging [55]. Group "iii", referred to as a "bottom up" approach by Castaldi et al [108,109], was developed at the regional scale (e.g., in a loam belt region in Belgium and in the Gutland-Oesling region in Luxembourg [48] and Bavaria (Germany) [74]), at the national scale (e.g., Spain [75]), and then at the supranational, continental scales (e.g., European scale [57,76]) using the LUCAS alone [57,75,76] or in combination with a local database [74,77] and also at the scale of Canada using the CanSYS National Pedon Database [78]. As they are directly derived from the spectral features, we focus on the first three groups.…”
Section: Approaches Conducted and Their Performancesmentioning
confidence: 99%
“…They found that DWT was the optimal technique for denoising spectra prior to predicting soil organic matter. For multispectral satellite images, no pretreatment was carried out except for the spatial filtering of Landsat 5 spectra [74,78]. The centering of a Sentinel-2 reflectance spectrum was preferred, but in the case of a single-date approach only [49].…”
Section: Approaches Conducted and Their Performancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensing System (GEOS3), which built a soil image on the multi-petabyte catalog of satell imagery with planetary-scale cloud processing architecture of the Google Earth Engi [39]. The second example is the Soil Composite Mapping Processor (ScMAP) that del ered exposed soil masks that were run on high-performance local computing clusters [4 Leveraging the application of current multispectral EO data for mapping croplan soils several applications have been recorded on the regional [43][44][45], national [46], an continental scale [30]. A significant number of these studies were implemented in Bra [47], India [48], Indonesia [49], and China [50] since detailed information about soils abundant in those countries.…”
Section: The Temporal Dimensionmentioning
confidence: 99%
“…Leveraging the application of current multispectral EO data for mapping cropland soils several applications have been recorded on the regional [43][44][45], national [46], and continental scale [30]. A significant number of these studies were implemented in Brazil [47], India [48], Indonesia [49], and China [50] since detailed information about soils is abundant in those countries.…”
Section: The Temporal Dimensionmentioning
confidence: 99%